Profile of oral manifestations of graft versus host disease - Camargo, Julia Rahal de; Grossmann-Pereira, Halina; Mobile, Rafael Zancan; Torres-Pereira , Cassius Carvalho; Schussel , Juliana Lucena (Journal of Oral Diagnosis, 2025)
Objective: The objective of this cohort study was to evaluate patients previously diagnosed with oral lesions associated GVHD, aiming to characterize and describe the primary clinical presentations observed. Methods: A retrospective analysis of medical and dental records, alongside a photographic review, was conducted to assess the oral manifestations of GVHD in these patients. Results: The evaluation of medical records shows that GVHD affected more males (58.4%); The most affected age group was 21-50 years (55.6%); The most frequent lesion was hyperkeratotic plaque (76.4). The most common underlying disease was Fanconi Anemia (FA) representing 54.2%. Of these, 5.1% developed some malignant neoplasm, confirming the fact that patients with FA have a marked predisposition to carcinomas. Conclusion: It is evident that GVHD manifests itself in different ways in the oral cavity, therefore, knowing the clinical presentation of GVHD becomes important to determine the most appropriate treatment and to differentiate it from lesions with malignant potential.